The Millennium Droughts and Australian Agricultural Productivity Performance: A Nonparametric Analysis. Issue 5 (28th April 2020) - Chambers, Robert G.; Pieralli, Simone; Sheng, Yu
Abstract : With the turn of the century, Australian agricultural productivity growth slowed dramatically. We investigate the connection between this slowdown and climatic factors by comparing regional‐level growth patterns before and after the advent of the Australian Millennium Droughts. The analysis incorporates climatic variates directly into the productivity accounting framework to reflect the stochastic nature of agricultural production, and measured productivity growth is decomposed into four components: technological change, weather‐related change, input‐scale adjustment, and diffusion (adaptation). Nonparametric productivity measurement and statistical techniques are used to quantify and examine the patterns of the observed productivity slowdown. The analysis suggests that the primary determinant of the slowdown is not a slowdown in technological innovation but climatic‐related changes in the pattern and rate of diffusion of technological advances.